Rotordynamic Analysis of Gas Foil-Polymer Bearings Based on a Structural Elasticity Model of Polymer Layer along with Static-Load Deflection Tests - Jisu Park (Applied Sciences, 2021)
In this study, rotordynamic analysis is performed using a simple structural model for the polymer layer of gas foil-polymer bearing (GFPB) composed of an accumulated bump foil and a polymer layer with high structural damping. The simple model that considers the elastic behavior of a cylinder-shaped polymer layer is introduced, and the structural stiffness of the layer is estimated based on Hooke’s law for differential elements in the layer. In addition, the simple model is coupled with the structural stiffness of the bump foil in consideration with a series relationship, which represents the structural model of GFPBs. A GFPB with thickness of 2 mm is fabricated, and the structural model is validated via static-load deflection tests for the GFPB. As a result of model validation, the proposed model is found to be effective in predicting the elastic behavior under the lightly loaded condition of GFPB. Next, the static performances of GFPBs, namely, gas-film pressure, thickness, and journal positions with respect to different polymer layer thickness, are analyzed to evaluate rotordynamic stability of GFPBs. The results indicate that high thickness yields an increase in damping and a decrease in cross-coupled effects. Specifically, in this study, 3 mm-thick polymer gives the best stability performance given the predicted effective damping results. As a result, this work provides a reasonable model for structural elasticity of GFPBs and lays a foundation for the widespread use of GFPBs.